Do capital industrial ao capital intelectual - um breve estudo a partir da concepção de Karl Marx - Rothstein, June Maria Emeline M. do Barreiro (2002)
This dissertation is based on a bibliografluic research about the evolution of the capital, ranging from Karl Marx s concepts to Thomas Stewart s approaches. Our goal is to correctly understand the process of transformation of capital and its developments, focusing on the evolution of industrial society towards the so-called knowledge society, as well as on the new paradgm inteilectual capital in corporations, and on the new characteristics acquired by the workers in face ofthese facts.